Effect of Teaching Quality on Students' Satisfaction in Nigerian Tertiary Institutions: The Moderating Role of E-Learning Amid COVID-19 Recovery (Global Journal of Human-Social Science, 2023)
Education enterprise has suffered severe setbacks worldwide during the COVID-19 pandemic due to lockdowns and other COVID-19 protocols This study aims to examine the effect of teaching quality on student satisfaction in Nigerian tertiary institutions amid COVID-19 recovery with moderating role of e-learning The study collected 279 survey data from students of two tertiary institutions in Kano state using a convenience sampling technique The study finds that teaching quality is positively related to students satisfaction Similarly the results indicate that e-learning positively and significantly affects students satisfaction Furthermore the results show a positive but insignificant moderating effect of elearning on the relationship between teaching quality and students satisfaction The study concludes that teaching quality characterized by effective interaction with students in training them through communication technology contributed significantly to their satisfaction It is also concluded that a lack of familiarity with and limited access to e-learning technology contributed to the absence of empirical evidence to support the moderating effect of e-learning on the relationship between teaching quality and students satisfaction The findings provide a fertile ground for policymakers in the education industry to develop new policies that could promote quality teaching and e-learning in Nigeria s institutions for better results
Keywords: covid-19; e-learning; education; student satisfaction; teaching quality